2020 12th International Conference on Cyber Conflict (CyCon) 2020
DOI: 10.23919/cycon49761.2020.9131721
|View full text |Cite
|
Sign up to set email alerts
|

Legal Issues Related to Cyber Threat Information Sharing Among Private Entities for Critical Infrastructure Protection

Abstract: The menace of cyber attacks has become a concern for both the public and private sectors. Several approaches have been proposed to tackle the challenge, but an approach that has received widespread acceptance among cyber security professionals in both public and private sectors is cyber threat information (CTI) sharing. CTI refers to any information that can help an organisation identify, assess, monitor and respond to cyber threats. It includes indicators of compromise; tactics, techniques and procedures used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…Already, we have observed that organisational measures are very essential for enhancing CIP. To this end, we studied the legal issues related to cyber threat information (CTI) sharing among private entities for CIP in [19]. This is because CTI sharing has been proposed as an efficient and effective method for improving CIP.…”
Section: Discussionmentioning
confidence: 99%
“…Already, we have observed that organisational measures are very essential for enhancing CIP. To this end, we studied the legal issues related to cyber threat information (CTI) sharing among private entities for CIP in [19]. This is because CTI sharing has been proposed as an efficient and effective method for improving CIP.…”
Section: Discussionmentioning
confidence: 99%
“…A key theme which has been identified is that one of the challenges to solving CTI sharing is the establishment of a trust relationship between those entering a sharing relationship. Trusted relationships can take a long time to build and constant effort to sustain, i.e., they are hard to gain, and easy to lose [25]. Additinally, such relationships are difficult to build for untrusted participants [38].…”
Section: Barriers To Cti Sharingmentioning
confidence: 99%
“…Survey [10], highlights a number of legal and regulatory obligations that organisation in certain countries must meet. For example, in Germany Internet Protocol (IP) addresses are considered personal information and therefore any disclosure of CTI containing them must comply with German privacy laws [23]. However, in the UK IP addresses are not considered personal information and therefore can be freely shared.…”
Section: Legal and Regulatory Obligationsmentioning
confidence: 99%